Epidemiological Investigation and Etiological Analysis of a Cutaneous Anthrax Epidemic Caused by Butchering Sick Cattle in Guizhou, China - Li, Shijun; Ma, Qing; Chen, Hong; Liu, Ying; Yao, Guanghai; Tang, Guangpeng; Wang, Dingming (Frontiers in Public Health, 2020)
A suspected human cutaneous anthrax epidemic caused by butchering sick cattle occurred in Zhijin County of Guizhou Province, Southwest of China, in 2016. Epidemiological investigation and etiological analysis were performed to provide scientific basis for the source tracking of the epidemic. The epidemic was epidemiologically investigated and skin blister samples collected from patients and soil samples collected from the butchering spots were used for B. anthracis isolation. The suspicious B. anthracis isolates were identified using conventional methods and PCR, followed by genotyping using Multiple Locus Variable Number Tandem Repeats (VNTR) Analysis (MLVA-15) and canSNP. The genetic relationship of epidemic strains and isolates collected from other regions were analysed. Epidemiological investigation results showed that the patients may be infected by B. anthracis during butchering sick cattle. One suspected B. anthracis strain was isolated from blood samples and blister fluids, respectively. Conventional methods identified the two suspected isolates as B. anthracis, while PCR results showed that PA and CAP gene were positive in the two isolates. MLVA-15 showed that the MLVA profiles of the two isolates were 9-20-12-53-16-2-8-8-8-4-4-4-4-10-4, which is different from the MLVA profiles of representative strains from other regions. CanSNP analysis showed that the two strains belonged to cluster A.Br.001/002. Clustering analysis and Minimum Spanning Tree (MST) demonstrated that the two isolates were clustered with strains previously isolated from Guizhou Province. The results indicated that B. anthracis was the pathogen for this epidemic and the patients were infected during butchering the sick. The genetic characteristics and the relationship of the B. anthracis isolates to strains from other regions indicated that the epidemic was a local occurrence.